An Assessment of Community Intervention for Reduction of Waterborne Illnesses in Peshawar, Khyber Pakhtunkhwa, Pakistan - Mehboob, Gulrukh; Hassan, Assad; Shah, Saleem (Journal of Development Policy Research and Practice (JoDPRP), 2018)
Given the recent rise in the scarcity of clean drinking water in Pakistan and waterborne illnesses, a collaborative project between the Institute of Management Sciences (IMS) and Higher Education Commission (HEC) of Pakistan, took place in the city of Peshawar, Khyber Pakhtunkhwa. The aim of the study was to reduce waterborne illnesses by building knowledge and capacity of the communities to enable them to have clean drinking water without incurring high financial costs. A number of awareness seminars, along with health educational material, were delivered to the community through educational institutes. To analyse the effectiveness of the intervention, a pre-project and post-intervention phase through knowledge, attitude and practice (KAP) analysis was conducted to quantify the perceptions and knowledge of the community. The analysis showed that knowledge about waterborne illnesses increased from 52% to 87%, attitude change moved from 16% to 93%, whereas improvement in practices by adopting low cost measures for clean water increased from 15% to 68%. It can be concluded that awareness has positive impact on peoples’ behaviour, knowledge and practice, especially when educational institutes are actively involved in community uplift projects. Effectiveness of such initiatives can be assured by widening their scope with involvement of government and non-government agencies as they play a pivotal role in social uplift of communities. The scope of this article is related to the following SDG / SDGs.